Potential Relevance of Allium sativum, Psidium Guajava Linn & Brassica oleracea Var. Capitata Formulations in the Management of Diabetes Mellitus - Abubakr Adamu; Yahuza Muhammed; Umar Abdulbaseet; Muhammad Atiku; Jamila Mashi; Dayyabu Shehu (AlQalam Journal of Medical and Applied Sciences, 2023)
Background and aims. Diabetes mellitus (DM) is a significant global health concern and a leading contributor to mortality. It is characterized by both macrovascular and microvascular complications. Preventing the onset of diabetes and managing its associated complications are of utmost importance. In recent times, there has been a growing inclination towards the consumption of certain foods, driven by their recognized biological properties. The study aimed to evaluate the proximate composition and antioxidant vitamin content of formulations containing Allium sativum (garlic), Psidium guajava Linn (guava), and Brassica oleracea Var. Capitata (cabbage) and explore their potential relevance in diabetes management. Methods. Phytochemical analysis and proximate composition of different formulations were conducted. The formulations were assessed for protein, carbohydrate, moisture, fat, crude fiber, and ash content. The antioxidant vitamin content, including vitamins A, C, and E, was also measured. Results. The garlic-containing formulations exhibited the highest protein content), while the garlic-cabbage formulation had the highest carbohydrate content. Guava-containing formulations were rich in crude fiber, and the cabbage formulation had the highest ash content. The garlic:cabbage: guava formulation demonstrated the highest vitamin A and E content, while the garlic: cabbage formulation exhibited the highest vitamin C content. Conclusion. The formulations containing garlic, cabbage, and guava leaves displayed diverse proximate compositions and antioxidant vitamin profiles. The high protein content in garlic formulations suggests their potential benefits in diabetes management, while the lower carbohydrate and fat content in garlic: cabbage: guava formulations may be suitable for blood sugar and weight control. The presence of fiber and essential minerals in these formulations further supports their potential relevance in diabetes management. Incorporating these formulations into the diet may contribute to glycemic control, reduce oxidative stress, and support overall health in individuals with diabetes.